Identity Foreclosure, Athletic Identity, and College Sport Participation - Good, Alan J.; Brewer, Britton W.; Petitpas, Albert J.; Van Raalte, Judy L.; Mahar, Matthew T. (My University, 1993)
A study was conducted with 502 college students (246 non-athletes, 90 intramural athletes, and 166 intercollegiate athletes) to investigate the relationship between self-identity variables (i.e., identity foreclosure and athletic identity) and college sport participation. The researchers used two scales, the foreclosure subscale of the Objective Measure of Ego Identity Status (OM-EIS, Adams et al., 1979) and the Athletic Identity Measurement Scale (AIMS, Brewer et al., 1993). Results indicated that identity foreclosure and athletic identity increase with level of sport participation. Identity foreclosure was significantly lower for upperclass students than for underclass students among non-athletes, but not among intramural and intercollegiate student-athletes. No gender differences were found. These findings suggested that intercollegiate student-athletes may commit to the role of "athlete" without exploring alternative identities. Implications of the results for the academic and career development of student-athletes were discussed. "The results of this study imply that college student-athletes may identify strongly with the athlete role to the extent that they fail to explore alternative identities." - p. 8
Keywords: identity; career development